ICTs for Regional Trade and Integration in Africa - Souter, David; Adam, Lishan; Jagun, Abiodun; Tusubira, Tusu (World Bank, Washington, DC, 2014)
Trade is critically important to Africa's economic prospects, as a source of revenue, investment and employment, yet Africa's trade is highly fragmented and the weakness of its trade performance constrains growth and poverty reduction. Africa today generates only about 2.5-3.5 per cent of world trade. African countries mostly export primary commodities while importing manufactured goods, from Europe, North America or developing regions outside Africa. Only about 10 per cent of Africa's trade is exchanged within the continent, a much lower proportion than in other world regions. Small domestic markets, landlocked status and limited natural resources restrict the trade potential of many countries. These structural factors inhibit the development of manufacturing sectors which could supply both African and world markets. Trade barriers are strongest at critical points along the supply chain between producers and consumers of goods and services, particularly points of entry/exit between countries.